Effect of Bacterial Infection on Ghrelin Receptor Regulation in Periodontal Cells and Tissues - Nogueira, Andressa V. B.; Nokhbehsaim, Marjan; Damanaki, Anna; Eick, Sigrun; Beisel-Memmert, Svenja; Kirschneck, Christian; Schröder, Agnes; Cirelli, Thamiris [UNESP]; Leguizamón, Natalia D. P. [UNESP]; Cirelli, Joni A. [UNESP]; Deschner, James (MDPI, 2022)
The effect of bacterial infection on the expression of growth hormone secretagogue receptor (GHS-R) was investigated in periodontal cells and tissues, and the actions of ghrelin were evaluated. GHS-R was assessed in periodontal tissues of rats with and without periodontitis. Human gingival fibroblasts (HGFs) were exposed to Fusobacterium nucleatum in the presence and absence of ghrelin. GHS-R expression was determined by real-time PCR and immunocytochemistry. Furthermore, wound healing, cell viability, proliferation, and migration were evaluated. GHS-R expression was significantly higher at periodontitis sites as compared to healthy sites in rat tissues. F. nucleatum significantly increased the GHS-R expression and protein level in HGFs. Moreover, ghrelin significantly abrogated the stimulatory effects of F. nucleatum on CCL2 and IL-6 expressions in HGFs and did not affect cell viability and proliferation significantly. Ghrelin stimulated while F. nucleatum decreased wound closure, probably due to reduced cell migration. Our results show original evidence that bacterial infection upregulates GHS-R in rat periodontal tissues and HGFs. Moreover, our study shows that ghrelin inhibited the proinflammatory actions of F. nucleatum on HGFs without interfering with cell viability and proliferation, suggesting that ghrelin and its receptor may act as a protective molecule during bacterial infection on periodontal cells.
Keywords: Fusobacterium nucleatum; Ghrelin receptor; Human gingival fibroblast; Periodontal tissues; Periodontitis